2004
DOI: 10.1128/aem.70.3.1545-1554.2004
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Changes Induced by High Hydrostatic Pressure in Exponential- and Stationary-Phase Cells of Escherichia coli : Relationship with Cell Death

Abstract: The relationship between a loss of viability and several morphological and physiological changes was examined with Escherichia coli strain J1 subjected to high-pressure treatment. The pressure resistance of stationary-phase cells was much higher than that of exponential-phase cells, but in both types of cell, aggregation of cytoplasmic proteins and condensation of the nucleoid occurred after treatment at 200 MPa for 8 min. Although gross changes were detected in these cellular structures, they were not related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 38 publications
(35 reference statements)
4
78
0
Order By: Relevance
“…Krzyzaniak et al (36) reported DNA conformational changes in low-salt buffer when the solution was treated with high pressure at 600 MPa. Other researchers observed a condensation of E. coli nucleoids in response to high pressure at 200 MPa for 8 min (38). Reducing the transcription of dps in response to pressure may allow the chromosomal DNA to renature to its protective state without interruption by abundant DNA-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Krzyzaniak et al (36) reported DNA conformational changes in low-salt buffer when the solution was treated with high pressure at 600 MPa. Other researchers observed a condensation of E. coli nucleoids in response to high pressure at 200 MPa for 8 min (38). Reducing the transcription of dps in response to pressure may allow the chromosomal DNA to renature to its protective state without interruption by abundant DNA-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that the mechanism of DNA damage by heat was different for the spore and vegetative cell of B. subtilis (Uchida and Kadota, 1979). Cells in the log phase are more susceptible to injury than spores or cells in the stationary phase (Mackey, 1984;Mossel and van Betten, 1984;Manas and Mackey, 2004). Important properties of the substrate include the water content, the concentration and type of ions and pH, the oxidation-reduction potential, the gas atmosphere, the presence of protective agents, and contamination with other microorganisms.…”
Section: Factors Causing Injurymentioning
confidence: 99%
“…Condensation of nucleoids was also reported for L. monocytogenes (21) and L. plantarum (41). More recently, Mañas and Mackey (22) observed nucleoid condensation of E. coli cells in both exponential-and stationary-phase cells stained with DAPI. In addition, our TEM micrographs showed the appearance of dense clusters that correspond to aggregated cytosolic proteins and ribosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our TEM micrographs showed the appearance of dense clusters that correspond to aggregated cytosolic proteins and ribosomes. Such clumps have been reported for S. enterica (21), E. coli (22), and Leuconostoc mesenteroides (14). Table 1 presents an attempt to examine nucleoid condensation and protein aggregation in conjunction with microbial inactivation after different pressure treatments for 10 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation